Use of Laparoscopy in Pediatric Urology - Kim, Christina (MedReviews, LLC, 2005)
The goal of laparoscopy is to minimize patient morbidity while maintaining successful outcomes. The use of laparoscopy in urology has grown significantly over the past 30 years. Its use has been slower to gain acceptance in pediatrics than in the adult population. Laparoscopic orchidopexies and nephrectomies are commonly performed and have become widely accepted as alternatives to open surgery, if not the gold standard. The more technically demanding procedures, such as laparoscopic pyeloplasty, laparoscopic-assisted bladder reconstruction, and laparoscopic ureteral reimplantation, tend to be performed at selected centers and have yet to achieve widespread acceptance. As laparoscopy is applied more widely in pediatric urology, its potential benefits and drawbacks will be clarified.